How to Apply Excise Taxes to Fight Obesity - Petit, Patrick (IMF How To Notes; How-To Note ;, 2021)
Fighting the obesity epidemic has so far proven a difficult challenge, given the diversity of natural and processed foods, the complexity of food supply chains, and the fact that targeting excessive caloric consumption is far trickier than reducing overall consumption (as for tobacco). Nevertheless, efforts to curb caloric intake are gearing up and the experience from tobacco control has drawn much attention on a potential role for excise taxes in fighting obesity. Many related questions have therefore been raised as part of the IMF's capacity development work: Should excises on unhealthy food be used to fight obesity? If so, under what conditions? What are the product and market characteristics that would help identify the relevant tax bases and the rates at which to tax them? While acknowledging that the scientific evidence keeps evolving, this note summarizes the ongoing debate and practice on food excises and on their potential role as a policy tool to fight the obesity epidemic, with a view to assist policymakers in deciding whether to go forward, and if so, how. How to Apply Excise Taxes to Fight Obesity.